KEMAMPUAN PENGAWAS INTERNAL DAN GAYA KEPEMIMPINAN MEMODERASI PENGARUH PARTISIPASI PENGANGGARAN DAN PROFESIONALISME PADA SENJANGAN ANGGARAN PEMERINTAH PROVINSI BALI - Suarditha, I Nyoman Gde; Dwirandra, A.A.N Bagus; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
The purpose of this study was to determine the direct effect of budgetary participation, professionalism toward budgetary slack provincial government of Bali and the effect of budgetary participation, professionalism after moderating variables, namely the internal auditor capabilities and leadership style. Sampling this study using the sampling method aims to use sampling (purposive sampling). Data were collected using a survey method with questionnaire technique. The number of respondents of this study is 282 people. Testing the validity and reliability of the instrument variables used in this study have high levels of reliability and validity were acceptable. The results showed that participation budgets negative influence on budgetary slack, professionalism negative effect on budgetary slack, the internal auditor capabilities is able to weaken the influence of budgetary participation on budgetary slack, the internal auditor capabilities reinforce negative influence of professionalism on budgetary slack, leadership style strengthen negative influence of budgetary participation on budgetary slack, leadership style weaken the negative influence of rofessionalism on budgetary slack.
Keywords: budgetary slack, budgetary participation, professionalism, ability internal auditors and leadership styles